O processo de luto infantil: criança, família e suas interlocuções na perda de um familiar significativo - Olesiak, Luísa da Rosa (2023)
The bond with similar individuals is a constituent of the subject in their psyche, and from childhood, it assumes prominence for their development. Particularly, in the encounter with the loss of a significant family member, a threat to the child's psyche arises, affecting their previously consolidated world and the bond with the deceased, revealing possible marks and repercussions on their life and structuring. In this research, we sought to understand how the process of childhood grief presents itself in the loss of a significant family member and the implications that grieving for a family member can have on this experience. For this purpose, a clinical-qualitative research was conducted, with a descriptive and exploratory character. In order to have an understanding of grief as a process, a study of multiple cases was carried out using a longitudinal approach, aiming to follow the children and responsible family members in the initial experience of grief in two stages, with a six-month interval. Subjects who were in the second month after the loss up to the first year were considered for participation in the research. They were recruited through social networks and the educational services provided by the local government. Semi-structured interviews were conducted with the responsible family members of the children, and play interviews were conducted with the children, as data collection instruments. With the consent of the participants, all material was recorded and transcribed in full for later analysis using content analysis. Throughout the research, ethical principles outlined in Resolution 510 of April 7, 2016, from the National Health Council, which guides ethics in research involving human beings in the Humanities and Social Sciences, were respected. Five cases were considered, consisting of one child and up to two reference family members who experienced the loss of sibling, mother, father, and paternal grandmother figures. The thesis presented three articles, which respectively explored the consolidation of language in childhood grief through individual and collective resources in symbolic and imaginary processes, the elaboration of pain related to the loss of a significant figure and the grief for their family member through the construction of the child's roles to sustain family bonds, and finally, the subsequent transformations of grief in the psychological and socio-economic aspects, alongside the re-signification of life and self. It can be concluded that the process of childhood grief corresponds to a co-constructed language with significant environments for the child, ranging from their family to their network of friends and school. The psychological elaboration of the child seeks support from a safe place and identification with the deceased family member and the grieving individual in their family, as a condition for moving forward in the grieving process. The restructure of family bonds after the initial period of grief enables the passage through the macro-social challenges of loss and a return of investments in life.